2016
DOI: 10.1038/ejhg.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of the retinoid-related nuclear receptor (RORB) gene and epilepsy

Abstract: Genetic generalized epilepsy (GGE), formerly known as idiopathic generalized epilepsy, is the most common form of epilepsy and is thought to have predominant genetic etiology. GGE are clinically characterized by absence, myoclonic, or generalized tonic-clonic seizures with electroencephalographic pattern of bilateral, synchronous, and symmetrical spike-and-wave discharges. Despite their strong heritability, the genetic basis of generalized epilepsies remains largely elusive. Nevertheless, recent advances in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…The previous study of a family and four sporadic individuals with RORB epilepsies reported a broad phenotypic spectrum encompassing GGE, predominantly eyelid myoclonia with absence epilepsy, and DEE. Individuals in the study had a cognitive profile ranging from learning disabilities to severe ID . The phenotypes in these previously reported families are similar to what we have identified; however, they did not report any occipital epilepsies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The previous study of a family and four sporadic individuals with RORB epilepsies reported a broad phenotypic spectrum encompassing GGE, predominantly eyelid myoclonia with absence epilepsy, and DEE. Individuals in the study had a cognitive profile ranging from learning disabilities to severe ID . The phenotypes in these previously reported families are similar to what we have identified; however, they did not report any occipital epilepsies.…”
Section: Discussionsupporting
confidence: 78%
“…One example in the epilepsies is the identification of RORB , encoding the retinoid‐related orphan receptor β, which lies within the 9q21.13 microdeletion . There is only a single study reporting patients with pathogenic variants in RORB . The epilepsy phenotypes in this study varied from developmental and epileptic encephalopathies (DEEs) to photosensitive genetic generalized epilepsies, predominantly eyelid myoclonia with absence epilepsy associated with mild intellectual disability (ID) …”
Section: Introductionmentioning
confidence: 99%
“…We also found several CNVs that included the genes HNRNPU (1q44) and RORB (9p21.13), both recently associated with epilepsy . Microdeletions of the 1q43q44 critical region have been associated with ID, dysmorphism, abnormalities of the corpus callosum, and seizures .…”
Section: Discussionmentioning
confidence: 75%
“…We also found several CNVs that included the genes HNRNPU (1q44) and RORB (9p21.13), both recently associated with epilepsy. 28,[30][31][32] Microdeletions of the 1q43q44 critical region have been associated with ID, dysmorphism, The reported phenotype associated with each known epilepsy gene refers to the phenotype reported in the OMIM or, if not available, the citation indicated in the supplementary material (Table S2) (Table S6a). In our cohort, five patients carried CNVs mapping to the 1q43q44 critical region, and in addition to the HNRNPU gene, in two duplications and one deletion, the chromosomal rearrangement included also the AKT3 gene, which might contribute to brain abnormalities observed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lhx2 has been shown to contribute to the differentiation of tanycytes and the maintenance of the mature state of Müller glia, two astrocyte-like cell types found in the hypothalamus and the retina, respectively (de Melo et al, 2012;Salvatierra et al, 2014), but Rorb, Dbx2 and Fezf2 have not been previously implicated in the development of glial cells. Interestingly, pathogenic mutations in RORB have been identified in genetic forms of epilepsy (Rudolf et al, 2016). Since astrocyte dysfunction is considered a key pathological mechanism in epilepsy (Patel et al, 2019), these RORB mutations may act by blocking the induction of mature astrocyte genes protecting from epileptogenesis (Patel et al, 2019), such as the Rorb target Glul, whose deletion in astrocytes in the mouse causes seizures and neurodegeneration (Zhou et al, 2019), or the glutamate transporter Slc1a2, which has been shown to be mutated in epileptic encephalopathies (Epi, 2016).…”
Section: Discussionmentioning
confidence: 99%